2014
DOI: 10.20286/jech-010351
|View full text |Cite
|
Sign up to set email alerts
|

Regular Breakfast Consumption and its Predictors Based on the Social Cognitive Theory in Female Students of Hamadan University of Medical Sciences

Abstract: Background and Objectives: Despite associating regular breakfast consumption habits with a range of health benefits, the rate of skipping the meal is high. The present study was conducted to determine the factors associated with breakfast consumption among female students of Hamadan University of Medical Sciences based on the Social Cognitive Theory (SCT). Materials and Methods: The present cross-sectional study was carried out on 423 female students in different faculties of Hamadan University of Medical Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…For example, studies of Salimi et al, showed that variables of this theory could explain 64% of the variance of eating breakfast among female students. This study also showed that among SCT theory's structure, self-efficacy and social support were the significant predictors of breakfast consumption (16).…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…For example, studies of Salimi et al, showed that variables of this theory could explain 64% of the variance of eating breakfast among female students. This study also showed that among SCT theory's structure, self-efficacy and social support were the significant predictors of breakfast consumption (16).…”
Section: Introductionsupporting
confidence: 54%
“…The study of Salimi et al, showed that social support is an important factor in predicting the frequency of eating breakfast with female students (16). Therefore, in order to facilitate intervention performance and making changes in these factors through friendship, this intervention was done in the dormitory.…”
Section: Educational Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the previous study[ 16 ] and the related formula the sample size was considered to be 288 individuals and then increased to 320 people taking into account a 10% drop-out rate ( d = 0.05, P = 0.25). Inclusion criteria were included voluntary and informed consent to participate in the study.…”
Section: Methodsmentioning
confidence: 99%